Hotels involvement in sustainable tourism practices in Klang Valley, Malaysia - Abdu Bakori, Kasimu; Samdin, Zaiton; Hassan, Hamimah (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
The hotel sector has been described as an industry of which activities constitute a great impact on the environment. Hotels consume vast amount of energy, water and non-durable goods, and has been reported to discharge huge amount of raw and solid waste in different quantities. Serious impacts on the environment were highlighted, calling for greater hotel’s participation in sustainable tourism practices by committing to environmental management system (EMS). Comprehensive studies among hotels in Malaysia on their contributing efforts in curbing environmental degradation have been inadequate. Hence, a current study was conducted and this paper presents findings on sustainable tourism practices most commonly adopted by Malaysian hotels within Klang Valley. The main findings indicate the use of occupancy sensor/key card control system as energy saving measures, as well as the use of energy-efficient equipments and products. This result, therefore, confirms a number of preliminary studies which indicates widespread adoption of energy management among hotels. Adopting these practices has enabled Malaysian hotels to benefit from improved image to the guests and the local communities as well as the enhancement of a safe and healthy environment for hotel guests and employees.